Intraamniotic Infection Rates after Intrauterine Pressure Catheter with and without Amnioinfusion - Mokhtari, Neggin; Wang, Tiffany; DiSciullo, Alison; Iqbal, Sara N.; Kawakita, Tetsuya (American Journal of Perinatology, 2020)
Objective This study aimed to examine the rates of intraamniotic infection between intrauterine pressure catheter with amnioinfusion and intrauterine pressure catheter alone.Study Design This was a retrospective cohort study of all women who had an intrauterine pressure catheter placement during labor at a tertiary referral hospital from January 2016 to June 2018. Outcomes were compared between women who had an intrauterine pressure catheter with amnioinfusion and intrauterine pressure catheter placement alone. The primary outcome was the rate of intraamniotic infection. Secondary outcomes included postpartum endometritis, postpartum hemorrhage (blood loss of ≥1,000 mL), quantitative blood loss (mL), and cesarean delivery. Multivariable logistic regression analysis was performed to calculate adjusted odds ratios (aOR) and 95% confidence interval (95% CI), controlling for age, race, body mass index, gestational age, and length of time of rupture of membranes.Results Of 1,268 women with an intrauterine pressure catheter, 298 (23.5%) also had an amnioinfusion. Women who had amnioinfusion through an intrauterine pressure catheter compared with those who had intrauterine pressure catheter alone had similar rates of intraamniotic infection (5.4 vs. 8.0%, crude p = 0.12, aOR 0.69; 95% CI 0.39–1.21), as well as secondary outcomes such as postpartum endometritis (3.0 vs. 2.5%, crude p = 0.61, aOR 1.12; 95% CI 0.49–2.53), postpartum hemorrhage (16.1 vs. 15.8%, crude p = 0.89, aOR 1.07; 95% CI 0.75–1.54), blood loss (479.5 vs. 500 mL, adjusted p = 0.89), and cesarean delivery (40.6 vs. 43.1%, crude p = 0.45, aOR 0.90; 95% CI 0.68–1.19).Conclusion Amnioinfusion was not associated with increased odds of intraamniotic infection compared with intrauterine pressure catheter placement alone.Key Points
Keywords: amnioinfusion; intrauterine pressure catheter; intraamniotic infection; chorioamnionitis; postpartum hemorrhage